1989
DOI: 10.1079/bjn19890133
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance in rats given chronic hormone treatment

Abstract: 1. Sprague-Dawley rats were injected for 16 d with long-acting insulin, and energy balance was calculated using the comparative carcass technique. Two experiments were carried out with females (starting weights 150 and 90 g respectively), and one with males (starting weight 150 8). In a fourth experiment, cytochrome c oxidasc (EC 1 .9.3.1) activity was measured as an indicator of the capacity for substrate oxidation. 2.Insulin increased weight gain by up to 57% ( P < 0.01 for all studies). Metabolizable energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…39, 40, 41, 42, 43, 44, 45 Notably, only a study by Vanderweele 46 showed an 11% reduction of spontaneous daily food intake in normal-weight chow-fed rats administered 2 U per day of regular insulin via an osmotic minipump implanted into the peritoneal cavity. Thus, our findings with insulin Det appear to be fundamentally novel.…”
Section: Discussionmentioning
confidence: 99%
“…39, 40, 41, 42, 43, 44, 45 Notably, only a study by Vanderweele 46 showed an 11% reduction of spontaneous daily food intake in normal-weight chow-fed rats administered 2 U per day of regular insulin via an osmotic minipump implanted into the peritoneal cavity. Thus, our findings with insulin Det appear to be fundamentally novel.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mean GH values for the females were similar to those reported by Hornick and colleagues (1998) and Cabaraux and colleagues (2003b), in young fattening BB males, the increase of plasma GH however remains unexplained, as was the decrease of insulin concentration at the end of finishing. Indeed, insulin concentration is positively related to fat accretion rather than protein accretion (Spencer, 1985; Woodward and Emery, 1989; Schwarz et al., 1992). These observations thus appears contradictory but could be explained by feeding behaviour alterations at the end of finishing, as a result of a satiety phenomenon in animals showing an innate inclination to deposit very low amounts of fat.…”
Section: Discussionmentioning
confidence: 99%
“…This was not surprising since there is no convincing evidence that insulin exerts positive effects upon muscle growth (Grizard et al, 1988;Reeds and Davis, 1992). The high insulin concentration may have been related to increased accretion of fat rather than protein (Spencer, 1985;Woodward and Emery, 1989;Schwarz et al, 1992). Insulin is the endocrine substance most associated with adipocyte function.…”
Section: Discussionmentioning
confidence: 99%